Peer Tutoring Sebagai Metode Pendidikan Berkemajuan dalam Meningkatkan Baca Al-Qur’an (Studi Kasus: SMKN 29 Jakarta) - Vito Alrahmado; Shobah Shofariyani Iryanti (Journal on Education, 2024)
In reality, currently, the system for learning to read the Al-Qur'an is not yet optimal and cannot create a conducive learning atmosphere. This results in a lack of students' understanding in learning to read the Al-Qur'an. Problems faced by students in reading the Qur'an include students who have low ability to recognize Hijaiyah letters, difficulty in distinguishing Hijaiyah letters such as (tsa-sa, dha-dza, tha-dzah) and difficulty distinguishing signs. read certain. To overcome this problem, researchers applied the method used in learning to read the Al-Qur'an, namely the peer tutoring method. This research aims to find out and analyze the extent to which the peer tutoring method can improve students' ability to read the Al-Qur'an. This research uses qualitative research with a case study approach method that focuses on two students in class XI EA 1 from SMK Negeri 29 Jakarta, which was carried out for a week from 20 to 26 November 2023 and data was collected through observation, interviews and tests. The research results prove that the peer tutoring method can significantly improve students' ability to read the Al-Qur'an, especially makharijul letters, short length, and reading fluency. The peer tutoring method is very effective in improving the ability to read the Al-Qur'an, especially for students who are not yet fluent in reading the Al-Qur'an. The learning process not only produces positive results, but also strengthens interpersonal relationships between tutors and students. And makes an important contribution in developing progressive educational approaches, especially in the context of learning to read the Koran.